ANALISA KEBUTUHAN LAHAN DAN KAPASITAS RUANG PARKIR RUMAH SAKIT UMUM PROPINSI DR. MOHAMMAD HOESIN PALEMBANG - Djaenudin Hadiyana; Sartika Nisumanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The parking area of Dr. Mohammad Hoesin Hospital is over capacity for cars because of that, the parking area had to along Dr. Moh. Ali Street which affected to traffic jam in arround Hospital area. The aims of this study are to find charateristic of parking are, to estimate parking are, to define parking issues. The analysis of this study using accumulation difference method and regression formula for parking area necessary. The result of this study is showed that maximum accumulation for motorcycle and cars, respectedly are 723 SRP and 608 SRP, while amounts of vehicle are 1779 and 1594 respectedly for motorcycle and car. Based on those, the entered of parking area is 1.287,5 m2. Analysis of parking area configuration is showed that configuration 30⁰ has 287 SRP, for 45⁰ has 315 SRP, for 60⁰ has 391 SRP, and for 90⁰ has 504 SRP, while a combined configuration has 540 SRP which is more effective than existing configuration. Based on the result of analysis, the parking area configuration in Dr. Mohammad Hoesin Hospital will be recommended to implementation of a combined configuration.Keyword: Parking, Parking Area, Parking Necessary